The study on the welfare management for elderly subsistence allowances. Social Development and Social Welfare Thung Khru District Office Bangkok Metropolitan Administration - suakasem, Siriwan (Journal of Humanities and Social Sciences Loei Rajabhat University, 2018)
This research aims to study and to guide the development of welfare management for elderly subsistence allowances. Social Development and Social Welfare Thung Khru District Office Bangkok Metropolitan Administration. The research found that 1. Elderly people who receive elderly subsistence allowances with community development and social welfare. Thung Khru District Office Bangkok Metropolitan Administration Mostly female. Age between 60-69 years old. Primary education. Marital status Other occupations (Unemployed housewife). Two children living with the family. Owning a home or residence and land is income and living in Thung Khru. 2. Welfare allowance for elderly people Social Development and Social Welfare Thung Khru District Office Bangkok Metropolitan Administration. Overall, it was found that the elderly had a high level of perception toward welfare management. When separating the opinion of the elderly on the side. Sort by average to descending order as follows. Service staff Process of site operation Satisfaction and public relations. Suggestions from the research. 1. Processes. Should set the stage Clear operation. 2. Service staff. Should develop human resource efficiency. Continuously. 3. Public relations. Should increase the information publicity. 4. The location should be adequate lighting, air, ventilation. 5. Satisfaction. The meeting should be organized to listen to the problems or complaints that occur during the operation.